ANALISIS KESALAHAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL MATERI PERSAMAAN GARIS LURUS - Ilma Nurfajriyah Insani; Tina Rosyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
In solving mathematics, of course, it cannot be separated from errors, both conceptual errors, principle errors and operating errors. This study aims to describe students' errors in solving straight line equations based on Kastolan's level of error. The research method used is descriptive qualitative research. The data collection tool in this study is a test question in the form of a description of 4 items of straight line equation material. The research data were then analyzed and described based on the Kastolan error rate. The subjects of this study were 16 students of class VIII SMP in one school in West Bandung Regency. The results of the analysis of student answers are that there are 40% student errors in conceptual errors, 56% student errors in principle errors, and 4% student errors in operating errors. The factors that became the student's error were (1) not understanding the meaning of the question and the use of the concept of variables; (2) Does not answer the question so that there is no solution; (3) not paying attention to the conditions in the application of the formula; (4) perform non-hierarchical/sequential settlements; and (5) errors in performing calculations.